Dispersion of an SH-Guided Wave in Weld Seam Based on Peridynamics Theory. (31st January 2020) - Zhang, Xiaolong; Xu, Zhenying
Abstract : The dispersion characteristics of shear horizontal- (SH-) guided waves in a weld seam are critical to identifying defects. By considering the force on the virtual boundary layer near the weld surface, a dispersion equation for the SH-guided wave in the weld seam was established here based on the peridynamics method. The wave dispersion equation is similar to the traditional theory. The SH wave in the infinite peridynamics medium has dispersion characteristics, and the group velocity of the SH-guided wave in the weld seam is slightly slower than that in the conventional theory. In the welded structure, the group velocity of the SH-guided wave is unevenly distributed in different regions due to the differences in material parameters between the weld seam and the steel plate and residual weld height on the weld seam. The distance from the different sensors to the defect can be precisely calculated via the group velocity distribution; thus, the defect can be accurately located. By compared with the finite element method and experiments under the same conditions, the reliability of the peridynamics method is verified. We used the group velocity of the SH-guided wave in the weld seam and peridynamics theory to better reflect the experimental conditions versus finite element simulations.